Emotional Blunting in Patients With Major Depressive Disorder: A Brief Non-systematic Review of Current Research - Ma, Hongzhe; Cai, Min; Wang, Huaning (Frontiers in Psychiatry, 2021)
Emotional blunting is frequently reported by patients with major depressive disorder (MDD) and has been identified as one of the most prominent side effects of antidepressants leading to medication discontinuation. However, antidepressant-induced emotional blunting remains largely unexplored—there lacks a clinical definition of this condition, and no agreeing conclusion has been reached regarding its etiology. Current research suggests that the onset of diminished emotional response may be related to antidepressant dose, with higher doses being more likely to induce emotional blunting. Consequently, most clinicians either reduce the dose or switch to another drug when treating this symptom. Overall, more comprehensive clinical assessments or interviews specifically designed to evaluate antidepressant-induced emotional blunting in MDD patients are in need to elucidate the neuropsychological mechanisms behind this increasingly prevalent symptom.